Phoxonic architectures for tailoring the acousto-optic interaction - N. Papanikolaou; I.E. Psarobas; G. Gantzounis; E. Almpanis; N. Stefanou; B. Djafari-Rouhani; B. Bonello; V. Laude; Martinez, A. (Proceedings of SPIE, 2011)
Periodic media offer impressive opportunities to manipulate the transport of classical waves namely light or sound. Elastic waves can scatter light through the so-called acousto-optic interaction which is widely used to control light in telecommunication systems and, additionally, the radiation pressure of light can generate elastic waves. Concurrent control of both light and sound through simultaneous photonic-phononic, often called phoxonic, bandgap structures is intended to advance both our understanding as well as our ability to manipulate light with sound and vise versa. In particular co-localization of light and sound in phoxonic cavities could trigger nonlinear absorption and emission processes and lead to enhanced acousto-optic effects. In the present communication, we present our efforts towards the design of different phoxonic crystal architectures such as three-dimensional metallodielectric structures, two-dimensional patterned silicon slabs and simple one-dimensional multilayers, and provide optimum parameters for operation at telecom light and GHz sound. These structures can be used to design phoxonic cavities and study the acousto-optic interaction of localized light and sound, or phoxonic waveguides for tailored slow light-slow sound transport. We also discuss the acousto-optic interaction in onedimensional multilayer structures and study the enhanced modulation of light by acoustic waves in a phoxonic cavity, where a consistent interpretation of the physics of the interaction can be deduced from the time evolution of the scattered optical field, under the influence of an acoustic wave.